Critical care nephrology - Ronco, Claudio; Bellomo, Rinaldo; Kellum, John A; Ricci, Zaccaria (Elsevier, 2018)
Comprehensive and clinically relevant, the third edition of 'Critical Care Nephrology' provides authoritative coverage of the latest advances in critical care procedures for patients with renal diseases or disorders. Using common guidelines and standardized approaches to critically ill patients, this multidisciplinary reference facilitates better communication among all physicians who care for critically ill patients suffering from kidney disease, electrolyte and metabolic imbalances, poisoning, severe sepsis, major organ dysfunction, and other pathological events.Shares a combined commitment to excellence lead by Drs. Claudio Ronco, Rinaldo Bellomo, John Kellum, and Zaccaria Ricci - unparalleled leaders in this field.